Transparent Oil–Water Separating Spiky SiO2 Nanoparticle Supramolecular Polymer Superhydrophobic Coatings. Issue 3 (22nd January 2023) - Nguyen, Nguyen Binh; Ly, Nguyên Hoàng; Tran, Huynh Nhu; Son, Sang Jun; Joo, Sang‐Woo; Vasseghian, Yasser; Osman, Sameh M.; Luque, Rafael
Abstract: A potential application of spiky SiO2 nanoparticles (NPs) with tubular and rough surfaces is investigated as superhydrophobic coatings, for their unique transparent, fluorinate‐free, and environmentally friendly properties. This study demonstrates a facile method for the successful fabrication of superhydrophobic coatings and SiO2 @polydimethylsiloxane (PDMS) using spiky SiO2 NPs, N ‐coordinated boroxines, and PDMS. Combined with spray coating technology, this method of superhydrophobic coating can be simply applied to both hydrophilic and hydrophobic surfaces, including wood, fabric, glass, metal, sponge, and paper. The nanocomposite coating on the glass surface showed both excellent superhydrophobicity and high transparency, with a contact angle of 165.4 ± 1.0° and 96.93% transmittance at 550 nm, respectively. SiO2 @PDMS‐modified glass substrate is found to be resilient to UV irradiation, water, and high temperature treatments at ambient conditions. Experimental data demonstrated that the simple but effective combination of N ‐boroxine‐PDMS and spiky SiO2 NPs produces a layered coating material that exhibits many good integrated surface properties, including stability, transparency, superhydrophobicity, and oil–water separation. Abstract : A facile method for the design of superhydrophobic coatings using spiky SiO2 nanoparticles, N ‐coordinated boroxines, and polydimethylsiloxane is reported herein, leading to excellent superhydrophobicity and high transparency as well as unprecedented self‐healing properties.